2022
DOI: 10.1021/jacs.2c07299
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hydrophobic/Hydrophilic Balance on Aggregation Pathways, Morphologies, and Excited-State Dynamics of Amphiphilic Diketopyrrolopyrrole Dyes in Aqueous Media

Abstract: We report the thermodynamic and kinetic aqueous self-assembly of a series of amide-functionalized dithienyldiketopyrrolopyrroles (TDPPs) that bear various hydrophilic oligoethylene glycol (OEG) and hydrophobic alkyl chains. Spectroscopic and microscopic studies showed that the TDPP-based amphiphiles with an octyl group form sheet-like aggregates with J-type exciton coupling. The effect of the alkyl chains on the aggregated structure and the internal molecular orientation was examined via computational studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 112 publications
1
37
0
1
Order By: Relevance
“…This observation indicated that the solid self-assembly predominantly occurred along the a -axis, where the intermolecular distances were reduced. The infrared (IR) absorption spectrum of the green-emissive 2D platelets showed prominent absorption peaks at 3006, 3030, and 3063 cm –1 (Figure S7), which are characteristic of intermolecular hydrogen bonds between the benzimidazole groups . Based on these results, we conclude that new hydrogen bonds were formed between neighboring fluorophores 1 after the release of 1-propanol, causing the aforementioned size changes.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…This observation indicated that the solid self-assembly predominantly occurred along the a -axis, where the intermolecular distances were reduced. The infrared (IR) absorption spectrum of the green-emissive 2D platelets showed prominent absorption peaks at 3006, 3030, and 3063 cm –1 (Figure S7), which are characteristic of intermolecular hydrogen bonds between the benzimidazole groups . Based on these results, we conclude that new hydrogen bonds were formed between neighboring fluorophores 1 after the release of 1-propanol, causing the aforementioned size changes.…”
Section: Resultsmentioning
confidence: 81%
“…The infrared (IR) absorption spectrum of the green-emissive 2D platelets showed prominent absorption peaks at 3006, 3030, and 3063 cm −1 (Figure S7), which are characteristic of intermolecular hydrogen bonds between the benzimidazole groups. 28 Based on these results, we conclude that new hydrogen bonds were formed between neighboring fluorophores 1 after the release of 1-propanol, causing the aforementioned size changes. Although this process did not result in crystal collapse in the small 2D platelets (Figure 2c), it caused some degree of destruction in the bulky crystals, rendering them unsuitable for single-crystal analysis.…”
Section: ■ Introductionmentioning
confidence: 68%
“…21 The most common strategy adopted for designing a self-assembly is the introduction of hydrophilic chains into a hydrophobic π-moiety for tuning hydrophobic/hydrophilic balance. 5 nine). 20,22,23 Other chromophores are also reported to form emissive aggregates such as perylene diimides, and porphyrins.…”
Section: Introductionmentioning
confidence: 98%
“…The design of photoluminescent organic nanostructure by self-assembly of π-conjugated molecules is highly challenging . Effective manipulation of intermolecular noncovalent interactions is crucial to attain unique nanostructures. The hydrophobic–hydrophilic balance thus dictates the nature of ordering of structures. Striking a such balance is being done by ticking the functional groups of monomers. Among the hydrophilic interactions, hydrogen bonding that is formed by the localized hydroxyl groups of monomers induced by temperature and pH of the medium offers a greater degree of control to tune the morphology vis-a-vis photonic properties of self-assembly. Hydrogen-bonded self-assembled nanostructures are omnipresent in living systems such as native protein, helical DNA, cellulosic fibers, and other derived structures. Inspired by their monomer structures, we have selected a natural product, pyrogallol as a precursor in synthesis of fluorescent monomer because it consists of localized hydroxyl groups that are capable of rapidly and robustly forming hydrogen bonds. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation